Linking leaf elemental traits to biomass across forest biomes in the Himalayas - Dyola, Nita; Liang, Eryuan; Peñuelas, Josep; Camarero, J. Julio; Sigdel, Shalik Ram; Aryal, Sugam; Lin, Wentao; Liu, Xiang; Liu, Yongwen; Xu, Xingliang; Rossi, Sergio (Science China-Earth Sciences, 2024)
Plants require a number of essential elements in different proportions for ensuring their growth and development. The elemental concentrations in leaves reflect the functions and adaptations of plants under specific environmental conditions. However, less is known about how the spectrum of leaf elements associated with resource acquisition, photosynthesis and growth regulates forest biomass along broad elevational gradients. We examined the influence of leaf element distribution and diversity on forest biomass by analyzing ten elements (C, N, P, K, Ca, Mg, Zn, Fe, Cu, and Mn) in tree communities situated every 100 meters along an extensive elevation gradient, ranging from the tropical forest (80 meters above sea level) to the alpine treeline (4200 meters above sea level) in the Kangchenjunga Landscape in eastern Nepal Himalayas. We calculated community-weighted averages (reflecting dominant traits governing biomass, i.e., mass-ratio effect) and functional divergence (reflecting increased trait variety, i.e., complementarity effect) for leaf elements in a total of 1,859 trees representing 116 species. An increasing mass-ratio effect and decreasing complementarity in leaf elements enhance forest biomass accumulation. A combination of elements together with elevation explains biomass (52.2% of the variance) better than individual elemental trait diversity (0.05% to 21% of the variance). Elevation modulates trait diversity among plant species in biomass accumulation. Complementarity promotes biomass at lower elevations, but reduces biomass at higher elevations, demonstrating an interaction between elevation and complementarity. The interaction between elevation and mass-ratio effect produces heterogeneous effects on biomass along the elevation gradient. Our research indicates that biomass accumulation can be disproportionately affected by elevation due to interactions among trait diversities across vegetation zones. While higher trait variation enhances the adaptation of species to environmental changes, it reduces biomass accumulation, especially at higher elevations.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Ecosystem function; Elevational gradient; Functional diversity; Functional traits; Leaf elements; Niche complementarity